The Reality Of Resorting To Inventing Islamic Financial Products And The Effect Of Their Application - Sebaa, Fatma Zahra (جامعة الوادي - University of Eloued, 2020)
This study discusses the role of financial innovation by focusing on further improving, developing and commercializing the product in general. In this context, we focus on Islamic finance as a financial system that is keen to encourage innovation in its products. We tried to address the issue of financial innovation for Islamic banking and finance and to review the most important models of innovation in Islamic financial products. Finally, we concluded by identifying the reflection of the innovations of Islamic financial products on economic development.
مقال
Keywords: Innovations, Financial Innovations, Islamic Finance, Islamic Finance Products, Islamic Banking.